1997
DOI: 10.1016/s0735-1097(97)00236-2
|View full text |Cite
|
Sign up to set email alerts
|

Nitric Oxide-Mediated Flow-Dependent Dilation Is Impaired in Coronary Arteries in Patients With Coronary Spastic Angina

Abstract: Our results indicate that flow-dependent coronary dilation is impaired in spasm arteries, partly due to a deficiency in endothelial nitric oxide bioactivity, which in turn may contribute to the increase in coronary tone during physiologic stimuli in patients with coronary spastic angina.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
74
0
3

Year Published

1999
1999
2015
2015

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 113 publications
(81 citation statements)
references
References 36 publications
4
74
0
3
Order By: Relevance
“…The causal, pathogenetic mechanisms of these two particular forms of angina are still largely unknown. Some potentially pathogenetic abnormalities, however, have been suggested to be present in both cases, including increased adrenergic function, 18,19 endothelial dysfunction, 20,21 and elevated endothelin-1 levels. 22 -24 Thus, it is possible that in our patients the same pathogenetic factors might have induced significant functional alterations in conductive and resistance coronary artery vessels.…”
Section: Discussionmentioning
confidence: 99%
“…The causal, pathogenetic mechanisms of these two particular forms of angina are still largely unknown. Some potentially pathogenetic abnormalities, however, have been suggested to be present in both cases, including increased adrenergic function, 18,19 endothelial dysfunction, 20,21 and elevated endothelin-1 levels. 22 -24 Thus, it is possible that in our patients the same pathogenetic factors might have induced significant functional alterations in conductive and resistance coronary artery vessels.…”
Section: Discussionmentioning
confidence: 99%
“…21,22 In the present study, we showed that endothelium-dependent FMD was decreased in vasospastic angina patients compared with control subjects, thus confirming the impaired vascular endothelial function in these patients and in agreement with previous reports. 11,12 Furthermore, of the 3 CCBs, only benidipine, a dihydropyridine, provided a significant improvement in endotheliumdependent FMD and plasma cGMP concentration in patients with coronary vasospasm. Diltiazem and verapamil, nondihydropyridine-type CCBs, had no effect on FMD or cGMP.…”
Section: Discussionmentioning
confidence: 99%
“…'~~-'~~ Thirty-eight percent of patients with angina pectoris at rest and 20% of patients with recent myocardial infarction have coronary artery spasm.128 Coronary spasm causes transient reductions of coronary artery blood flow in the absence of increases in myocardial oxygen demands and is associated with electrocardiographic ST-segment elevation or depression indicative of acute myocardial ischemia. 129 Spasm may occur either at sites of atherosclerotic coronary stenosis or in regions of the coronary vasculature where no stenosis exists. Often intravenous ergonovine maleate, methacholine, histamine, cold-pressor testing, or hyperventilation can induce coronary artery spasm.lZ8 Moreover, the response to these provocative tests is markedly increased in patients with hyperlipidemia.…”
Section: Coronary Spasmmentioning
confidence: 99%
“…l27. 129 The coronary concentration of vasoconstrictor aponists is increased in these patients due to coronary endothelial platelet aggregation which releases serotonin and thromboxane A2. Serotonin is also taken up into the pericoronary sympathetic nerve terminals.…”
Section: Coronary Spasmmentioning
confidence: 99%